Community Service regarding the importance of giving birth in health facilities in Cijakan Village, Bojong District, Pandeglang Regency, Banten in 2023 - Mulianti, Amanda Eka Mulianti; Shinta Novelia; Putri, Amelia; Faradilla Puteri Rochayu; Ami Rachyani; Juninda Putri; Laila Hanif Assyuri; Rahayu Indah Lestari; Ricke Muriadi (International Journal of Community Services, 2024)
Background: Health problems receive serious attention from various elements of society. One way to overcome health problems in society is to carry out community service. Community service is an activity that aims to help the community overcome the problems they face by actively participating in the health development process and increasing community empowerment. Objective: Carry out community service by carrying out activities ranging from assessment to intervention and evaluation of field activities. So that it can build public knowledge so they can live healthier, safer and more prosperous lives. Method: Community Midwifery Practice has been carried out by National University Midwife Professional Education Students in Cijakan Village, Bojong District, Padeglang Regency, Banten. with stages: Orientation, secondary data collection, Village Community Deliberation (MMD), Action Planning (POA), intervention activities in the form of counseling on "The importance of giving birth with health workers" and implementation of free pregnancy checks (ANC) and ending with Evaluation, Closing. Results: Community service activities in the form of counseling "The importance of giving birth with health workers" and free pregnancy checks (ANC) went smoothly. The public can understand and understand the explanation given, marked by input from the people present. Conclusion: Community service activities in the form of outreach to pregnant women and women of childbearing age (WUS), where health information is provided about "The importance of giving birth with health workers" is expected to make pregnant women and WUS better understand the importance of giving birth safely in health facilities.